2005
DOI: 10.1037/0022-3514.89.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Separating Multiple Processes in Implicit Social Cognition: The Quad Model of Implicit Task Performance.

Abstract: The authors argue that implicit measures of social cognition do not reflect only automatic processes but rather the joint contributions of multiple, qualitatively different processes. The quadruple process model proposed and tested in the present article quantitatively disentangles the influences of 4 distinct processes on implicit task performance: the likelihood that automatic bias is activated by a stimulus; that a correct response can be determined; that automatic bias is overcome; and that, in the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
387
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 475 publications
(405 citation statements)
references
References 65 publications
12
387
2
4
Order By: Relevance
“…However, recent research has shown that implicit measures are not as process-pure as researchers have hoped (e.g., Sherman, 2006). In particular, even implicit measures are influenced by the motivation and the ability to control the impact of activated associations on open responses (Conrey, Sherman, Gawronski, Hugenberg, & Groom, 2005;Payne, 2001;Payne & Bishara, 2009;Sherman et al, 2008). For instance, restraining cognitive resources or using time pressure leads to higher scores on these measures, not because stereotypes are activated more strongly, but because people are less able to exhibit control (e.g., Conrey et al, 2005;Govorun & Payne, 2006).…”
Section: Measures Of Stereotype Activation and Stereotype Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent research has shown that implicit measures are not as process-pure as researchers have hoped (e.g., Sherman, 2006). In particular, even implicit measures are influenced by the motivation and the ability to control the impact of activated associations on open responses (Conrey, Sherman, Gawronski, Hugenberg, & Groom, 2005;Payne, 2001;Payne & Bishara, 2009;Sherman et al, 2008). For instance, restraining cognitive resources or using time pressure leads to higher scores on these measures, not because stereotypes are activated more strongly, but because people are less able to exhibit control (e.g., Conrey et al, 2005;Govorun & Payne, 2006).…”
Section: Measures Of Stereotype Activation and Stereotype Applicationmentioning
confidence: 99%
“…In particular, even implicit measures are influenced by the motivation and the ability to control the impact of activated associations on open responses (Conrey, Sherman, Gawronski, Hugenberg, & Groom, 2005;Payne, 2001;Payne & Bishara, 2009;Sherman et al, 2008). For instance, restraining cognitive resources or using time pressure leads to higher scores on these measures, not because stereotypes are activated more strongly, but because people are less able to exhibit control (e.g., Conrey et al, 2005;Govorun & Payne, 2006). Furthermore, participants high in the motivation to control prejudice show lower scores on implicit measures, partly due to the fact that they are more motivated and better able to exert control over stereotypic response tendencies (Gonsalkorale, Sherman, Allen, Klauer, & Amodio, 2011;Payne, 2005).…”
Section: Measures Of Stereotype Activation and Stereotype Applicationmentioning
confidence: 99%
“…First, we wanted to compare the predictive validity and reliability of the IAT and EPT. Although both measures are referred to as "implicit attitude measures," the underlying mechanisms that drive performance in these tasks are known to be quite different (see Conrey et al 2005;Klauer et al 2007;Spruyt et al 2007c). Unlike the EPT, for example, the IAT is sensitive to salience asymmetries (e.g., Rothermund and Wentura 2004), recoding processes (e.g., Rothermund et al 2009), and automatically activated extra-personal associations (Karpinski and Hilton 2001).…”
mentioning
confidence: 99%
“…The traditional index of automatically activated associations from the IAT (D-score) is influenced by cognitive processes in addition to automatic processes (Conrey et al, 2005). In prior work, we used the Quad Model, which is a multinomial processing tree model, to distinguish four cognitive processes that influence SC-IAT performance.…”
Section: Measures Single Category Implicit Association Test (Time 1)mentioning
confidence: 99%